Qualitative and Quantitative Analysis on Flavonoid Distribution in Different Floral Parts of 42 Hemerocallis Accessions - Li, Sen; Cui, Huliang; Wang, Jinyao; Hou, Feifan; Xiong, Xiong; Kang, Xiuping; Xing, Guoming (Frontiers in Plant Science, 2021)
The Hemerocallis species is widely consumed as nutritious vegetable and traditional medicine in eastern Asia and used as an ornamental flower worldwide. Compared with most other horticultural products, its flower is richer in polyphenols, flavonoids, carotenoids and anthocyanins. Therefore, the flower has strong antioxidant activity that inhibits cancer cell proliferation, which could used for health and pharmaceutical purposes. The flavonoids composition and distribution in the flowers, and the content differences between different accssions is still unclear. In this context, there were seven flavonols, two flavones, and two anthocyanins in Hemerocallis flower which were determined by high-performance liquid chromatography (HPLC) coupled with photodiode array and mass spectrometric detectors. Rutin was the dominant flavonol, and its content in the petal was higher than that of the sepal. Isorhamnetin 3-rutinside, quercetin 7-glucoside, and kaempferol 3-glucoside were the dominant flavonols. Cyanidin 3,5-glucoside and cyanidin 3-rutinside were the major anthocyanins, resulting in flower petal coloration, and the petal had higher contents than sepal. Hierarchical cluster analysis grouped the 42 varieties into four groups, and they were significantly different (p<0.05) from each other in the ten significant compounds by One-way ANOVA. Overall, the qualitative and quantitative analysis of flavonoid constituents in six floral organ parts of 42 Hemerocallis accessions were elucidated, which could be helpful for the food and pharmaceutical industries.